Diethyl Aminoethyl Hexanoate Priming Ameliorates Seed Germination via Involvement in Hormonal Changes, Osmotic Adjustment, and Dehydrins Accumulation in White Clover Under Drought Stress - Hassan, Muhammad Jawad; Geng, Wan; Zeng, Weihang; Raza, Muhammad Ali; Khan, Imran; Iqbal, Muhammad Zafar; Peng, Yan; Zhu, Yongqun; Li, Zhou (Frontiers in Plant Science, 2021)
Drought is an important byproduct of climate change reducing the productivity of forage species under arid and semi-arid conditions worldwide. DA-6, a novel plant growth regulator, has proven to be involved in the amelioration of critical physiological functions in many agricultural crops under various abiotic stresses, but the role of the DA-6 in alleviating drought-induced seed germination inhibition has never been investigated. The present study was carried out to elucidate the impact of the DA-6 priming on seeds germination of white clover under drought stress. Results showed that seed priming with DA-6 significantly mitigated the drought-induced reduction in germination percentage, germination vigor, germination index, seed vigor index, root length, shoot length, fresh weight, and dry weight after seven days of seed germination. The DA-6 significantly increased the endogenous indole-3-acetic acid, gibberellin, and cytokinin content with marked reduction in abscisic acid content in seedlings under drought stress. In addition, DA-6 significantly accelerated starch catabolism by enhancing the activities of hydrolases contributing towards enhanced soluble sugars, proline content and ameliorated the antioxidant defense system to enhance the ability of ROS scavenging under drought stress. Furthermore, exogenous DA-6 application significantly increased dehydrins accumulation and upregulated transcript levels of genes encoding dehydrins (SK2, Y2SK or DHNb) during seeds germination under water deficient condition. These findings suggested that the DA-6 mediated seeds germination and drought tolerance associated with changes in endogenous phytohormones resulting in increased starch degradation, osmotic adjustment, antioxidants activity, and dehydrins accumulation during seed germination under water deficient condition.